2009
DOI: 10.1016/j.ijgo.2009.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Rectal misoprostol versus intravenous oxytocin for prevention of postpartum hemorrhage

Abstract: Routine use of 800 microg of rectal misoprostol was effective in reducing blood loss after delivery. We recommend the regimen for low-resource, busy obstetric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…In the present trial, no differences in the number of cases of PPH and additional oxytocin usage were observed. This finding is in keeping with several other studies [8,12,14,15,20–22]. However, a WHO multicenter randomized trial [10] found a significant difference: 20% of women given misoprostol had a measured blood loss of at least 500 mL, compared with 14% of those given oxytocin (RR 1.44, 95% CI 1.35–1.54; P < 0.001).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present trial, no differences in the number of cases of PPH and additional oxytocin usage were observed. This finding is in keeping with several other studies [8,12,14,15,20–22]. However, a WHO multicenter randomized trial [10] found a significant difference: 20% of women given misoprostol had a measured blood loss of at least 500 mL, compared with 14% of those given oxytocin (RR 1.44, 95% CI 1.35–1.54; P < 0.001).…”
Section: Discussionsupporting
confidence: 88%
“…Shivering, pyrexia, and diarrhea were the most common adverse effects in the present study and were significantly more prevalent among women in the misoprostol group. This is a common finding in many studies that have compared misoprostol with oxytocin [8–10,14,15,18,20–23], although Afolabi et al [13] reported no rise in temperature between the pre‐intervention and post‐intervention periods in either group in their study in Ile‐Ife, Nigeria. The pathogenesis of shivering and pyrexia associated with misoprostol is related to a prostaglandin‐mediated shift in the hypothalamic set point of the thermoregulatory pathway.…”
Section: Discussionmentioning
confidence: 92%
“…The risk of bias was assessed independently by LH and AW for 14 trials [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Six assessments [24][25][26][27][28][29] were produced during a review by Gallos et al [30]. [47].…”
Section: Risk Of Bias Of Included Trialsmentioning
confidence: 99%
“…In an Egyptian study it was shown that routine use of 800 microgram of rectal misoprostol was effective in reducing blood loss after delivery. 10 The major advantages of utilizing rectal misoprostol include its ease of administration, low side effect profile and its ability to be administered in patients experiencing vomiting during intrapartum period. 11 In our country, the rate of caesarean delivery is increasing, so reduction of blood loss at caesarean section is beneficial to the patients in terms of decreased postoperative morbidity and a decrease in risks associated with blood transfusion.…”
Section: Mediscopementioning
confidence: 99%